Study and modeling of hydrogen release from Ti, Zr, Ni, Pd, Pt during linear heating; International Journal of Hydrogen Energy; Vol. 46, iss. 37 - Tyurin Yu. I. Yuri Ivanovich; Nikitenkov N. N. Nikolai Nikolaevich; Sypchenko V. S. Vladimir Sergeevich; Zhang Hongru; Ma Syaole (2021, 2021)
Title screen